Validation of the spanish version of the pediatric lower urinary tract symptoms scale (PLUTSS) - (:unkn) unknown (INIESTARES, S.A., 2017)
OBJECTIVES: Lower Urinary Tract Dysfunction (LUTD) is the most common clinical problem in pediatric urology. To our knowledge non-validated instruments properly designed to screen lower urinary tract symptoms in the pediatric population has been translated and adapted to Spanish population. Pediatric Lower Urinary Tract Symptoms Score (PLUTSS) has proven to be a valid questionnaire for screening and evaluation of the response of children with LUTD to therapy. The aim of this study was to validate the PLUTSS questionnaire into Spanish, and put it to clinical use in pediatric patients, with cross-cultural equivalence to the original version. METHODS: The PLUTSS questionnaire was validated between February 2015 and February 2016. The Spanish version was obtained by using the forward/back-translation method with expert, bilingual translator, complying with the ISPOR principles. The questionnaire was administered to 80 patients with either lower urinary tract symptoms (40) or without any urological complaints (40). A descriptive statistical analysis of interscale correlation was performed. To confirm reliability, test-retest reliability was assessed by intro-class correlation coefficient, and the internal consistency was assessed by Cronbach's alpha coefficient. ROC curve was used to define cutpoint and its validity in discrimination between groups. RESULTS: The median of the two groups was significantly different: 20.53 (patients with LUTD) vs 3.27 (controls). Internal consistence of the 13-item scale (without quality of life item) was high: Cronbach's alpha coefficient 0.827. The test-retest analysis of reproducibility showed an intro-class correlation coefficient of 0.997 (95% IC: 0.994-0.999) (p<0.0001). CONCLUSIONS: The Spanish version of the PLUTSS questionnaire has proven to be acceptable and culturally equivalent to the original version. It has a good degree of consistency, validity and reliability PLUTSS showed a high power to discriminate patients with LUTD.
Keywords: Lower Urinary Tract Dysfunction; Symptoms Score; Pediatric; Lower Urinary Tract Symptoms; VOIDING-SCORING-SYSTEM; VESICOURETERAL REFLUX; CHILDREN; INCONTINENCE; DYSFUNCTION; POPULATION; STANDARDIZATION; QUESTIONNAIRE; TRANSLATION; INSTRUMENT